2017
DOI: 10.1002/apj.2142
|View full text |Cite
|
Sign up to set email alerts
|

An investigation on simultaneous effects of several parameters on the demulsification efficiency of various crude oils

Abstract: The current study aims to investigate the simultaneous effects of a novel magnetic demulsifier concentration as well as operating temperature on the demulsification efficiency of three different aboriginal samples of Persian Gulf, namely, light, medium, and heavy crudes. In this regard, TOMAC‐Fe3O4‐SiO2 (MT) was chosen as the magnetic nano‐modified demulsifier. The optimum concentrations of MT were obtained to be 0.98, 0.99, and 1.1 ppm, while the optimum operating temperatures determined were 38.2, 45.2, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…However, when SiO 2 , CNTs, and Ox-CNTs were added into the emulsion, respectively, there was no water separation phenomenon. A possible explanation for this is that these nanomaterials cannot improve the flocculation and coalescence enough between water droplets and overcome the inhibition of the interface film. , The experimental results indicate that the emulsion could exist for a long time.…”
Section: Resultsmentioning
confidence: 96%
“…However, when SiO 2 , CNTs, and Ox-CNTs were added into the emulsion, respectively, there was no water separation phenomenon. A possible explanation for this is that these nanomaterials cannot improve the flocculation and coalescence enough between water droplets and overcome the inhibition of the interface film. , The experimental results indicate that the emulsion could exist for a long time.…”
Section: Resultsmentioning
confidence: 96%
“…These data indicated that TGHA gave a higher DP than PGHA, while CD achieved the highest DP. An increase in temperature causes viscosity reduction, enhancing the kinetic energy of droplets and increasing the difference in the density of water and crude oil, contributing to effective coalescence and aggregation of water droplets and phase separation …”
Section: Resultsmentioning
confidence: 99%
“…An increase in temperature causes viscosity reduction, enhancing the kinetic energy of droplets and increasing the difference in the density of water and crude oil, contributing to effective coalescence and aggregation of water droplets and phase separation. 36 3.2.4. Demulsification Time (DT) Effect.…”
Section: Water Content Effectmentioning
confidence: 99%
“…Previous experiences (e.g., [5][6]) document that corrosive properties of water-soluble salts can cause significant damage to operating equipment (e.g., pipes, valves, pumps, tanks, and tanker vessels) as well as internal parts of refinery distillation towers. Impurities may cause fouling on interior surfaces of the equipment, thus potentially leading to clogging of the oil heater pipes and increase of temperature and pressure therein, with critical implications on energy use.…”
Section: Introductionmentioning
confidence: 99%